STRATEGI MARKETING MIX SYARI’AH DALAM MENINGKATKAN PENJUALAN (Studi Pada Nanda Cosmetik Kampung Merempan Hilir Kecamatan Mempura Kabupaten Siak) - Sri Indriyani Ali; Resa Maridawati (STAI Sulthan Syarif Hasyim, 2025)
This study discusses the implementation of sharia-based marketing mix strategies in an effort to increase sales at Nanda Cosmetics, located in Merempan Hilir Village, Mempura District, Siak Regency. The main objective of this study is to analyze how sharia marketing mix strategies can be implemented to increase sales of cosmetic products at Nanda Cosmetics Siak. The method used in this study is a qualitative approach with a descriptive method, which involves data collection through interviews, observations, and documentation. The subject of the study was the owner of the Nanda Cosmetics Siak business, namely Nanda Hidayah, while the object of the study focused on the sharia marketing mix strategy implemented to increase product sales at Nanda Cosmetics Siak. The results of the study indicate that the marketing mix strategy implemented by Nanda Cosmetics Siak follows the 5P principle, namely product, price, place, promotion, and sharia guidelines. In its implementation, the marketing mix strategy is in accordance with sharia principles. Where Nanda Cosmetics products already have a BPOM label that guarantees safety and suitability for Muslim consumers. Pricing is done fairly and not excessively, promotions are done honestly and in accordance with sharia principles. However, the location aspect still needs to be improved because currently it can only be reached by the surrounding community.